Chinese Petai Leaves (Leucaena leucocephala) as a Natural Therapy for Burn Wound Healing: A Literature Review - Sugiyarto, Sugiyarto; Rifai, Akhmad; Sumardino, Sumardino (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Burns can cause disruption of skin integrity which makes patients susceptible to infection. It has been reported that morbidity and mortality in this population are almost 61% caused by infection. One of the best and optimal treatments in this problem is to use complementary therapy that accelerates the healing of burns, namely by administering petai cina leaves topically. The source of the article used was obtained from a search through PubMed, ScienceDirect, and Google Scholar from 2015 to 2018. After being obtained, an article assessment was carried out until the stage of making a literature review. Based on the literature review that has been carried out, it was found that the use of petai cina leaves topically can accelerate the healing time of burns. This is also supported by the results of statistical tests from several studies which show that petai cina leaves are effective in accelerating the healing of burns with p 0.05. Petai cina leaves have the potential as a complementary nursing intervention for healing burns that supports the performance of the main pharmacological therapy for burns, although clinical trials have not been carried out on humans.